HUBUNGAN ANTARA KADAR SUPEROKSID DISMUTASE (SOD) DENGAN ARUS PUNCAK EKSPIRASI PADA ANAK ASMA - , Arie Kurniasih ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Asthmatic children have a risk to get asthma attack during their life. Asthma is a chronic inflammatory process which involve variety of cells such as inflammatory mediators, reactive oxygen species (ROS) and cytokines. The inflammatory process would be exacerbated in the presence of oxidative stress. Superoxide dismutase (SOD) is the first important enzyme to protect the respiratory tract against oxidative stress. SOD activity reduce during frequent asthma exacerbations due to increased of stress oxidant. The decreased of SOD has correlation with increased of airway obstruction and bronchospasm.Objective: To asses the correlation between the levels of SOD and peak expiratory flow, second objective was to determine the impact of level SOD in predicting asthma attack. Methods: A cross sectional study was conducted at Dr. Sardjito hospital on January to April 2011. Research subjects were asthmatic children aged 6 -18 years. Blood samples were taken to measure the level of SOD at the same time with peak expiratory flow measurement. The relationship between SOD levels and peak expiration flow was analyzed by pearson correlation. Multivariate analysis was done to determine variable affecting in peak expiratory flow. Prospective study was also performed, children were followed one month after the blood samples were obtained. Results: Of thirty-nine patients enrolled in this study. There was no correlation between levels of superoxide dismutase and peak expiratory flow, r (95% CI) = 0,289 (-0,025 â 0,47), p = 0,074. Age of asthmatic children has relation with peak expiratory flow, Ã (95%CI) = 0,5 (3,10 â 11,57), p = 0,01. There was lower level of superoxide dismutase caused a risk of asthma attack, RR (95% CI) = 5,5 (1,6 â18,9), p = 0,009. Conclusions: There was no relationship between the levels of superoxide dismutase with peak expiratory flow. This study showed no correlation between age and peak expiratory flow and the relationship between low SOD levels with risk of asthma attacks in the next month